Systematic analysis of genetic alterations in tumors using Cancer Genome WorkBench (CGWB) - Zhang, Jinghui; Finney, Richard P.; Rowe, William; Edmonson, Michael; Yang, Sei Hoon; Dracheva, Tatiana; Jen, Jin; Struewing, Jeffery P.; Buetow, Kenneth H. (Genome Research, 2007)
Systematic investigations of genetic changes in tumors are expected to lead to greatly improved understanding of cancer etiology. To meet the analytical challenges presented by such studies, we developed the Cancer Genome WorkBench (http://cgwb.nci.nih.gov), the first computational platform to integrate clinical tumor mutation profiles with the reference human genome. A novel heuristic algorithm, IndelDetector, was developed to automatically identify insertion/deletion (indel) polymorphisms as well as indel somatic mutations with high sensitivity and accuracy. It was incorporated into an automated pipeline that detects genetic alterations and annotates their effects on protein coding and 3D structure. The ability of the system to facilitate identifying genetic alterations is illustrated in three projects with publicly accessible data. Mutagenesis in tumor DNA replication leading to complex genetic changes in the EGFR kinase domain is suggested by a novel deletion–insertion combination observed in paired tumor–normal lung cancer resequencing data. Automated analysis of 152 genes resequenced by the SeattleSNPs group was able to identify 91% of the 1251 indel polymorphisms discovered by SeattleSNPs. In addition, our system discovered 518 novel indels in this data set, 451 of which were found to be valid by manual inspection of sequence traces. Our experience demonstrates that CGWB not only greatly improves the productivity and the accuracy of mutation identification, but also, through its data integration and visualization capabilities, facilitates identification of underlying genetic etiology.
10.1101/gr.5963407